Pengaruh Model Pembelajaran Inquiry Terhadap Hasil Belajar Kognitif Pjok Di SMP Negeri 1 Karawang Barat - Gumilang, Ryan Chandra; Dimyati, Akhmad; Susanti, Evi (Peneliti.net, 2025)
This study uses a quantitative approach, with experimental research methods. The purpose of this study is to find out how much the Inquiry Learning Model Affects the Cognitive Learning Outcomes of PJOK at SMP Negeri 1 Karawang Barat. This research was carried out at SMP Negeri 1 West Karawang. The population of this study is class VIII of SMP Negeri 1 West Karawang which totals 480 people. The sample used in this study was Cluster Random Sampling, after being drawn, the sample in the study was class VIII B which amounted to 30 people, VIII F 30 people and VIII A 23 people with a total sample of 83 people. The form of research design uses a one-group pre-test-postest design. This research instrument uses multiple-choice test instruments. The results of this study were that the average before and after treatment increased, namely the mean pre-test was 62.12 to the mean post-test 67.13. Meanwhile, the results of the hypothesis test calculation of the paired t-test test with the data obtained from this study were a significance value (2-tailed) 0.000 < 0.05, meaning that there was an influence of the pre-treatment value with the average value after treatment. It can be concluded that the Inquiry learning model can affect the cognitive learning outcomes of PJOK at SMP Negeri 1 West Karawang.